Rewilding : giving nature a second chance - Drake, Jane, 1954-; Love, Ann (Annick Press, 2017)
"A comprehensive look at the environmental movement of rewilding whereby habitats are restored to their natural states and native plants and animals are reintroduced to these habitats around the world."--